Voltammetric behavior of Zinc hexacyanoferrate (III) nanoparticles and their application in the detection of N-acetylcysteine - dos Santos, Vanessa Solfa [UNESP]; Maraldi, Vitor Alexandre [UNESP]; Bonfim, Kely Silveira [UNESP]; Souza, Tamires Rocha [UNESP]; Nakamura, Ana Paula Rizzato [UNESP]; Magossi, Maiara de Souza [UNESP]; Magossi, Mariana de Souza [UNESP]; Fernandes, Daniela Silvestrini [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Elsevier, 2017)
The present work reports the voltammetric behavior of Zinc hexacyanoferrate (III) nanoparticles and their application in the detection of N-acetylcysteine. Two distinct ratios of water/formamide 10:0 (ZnH-1) and 4:6 (ZnH-2) were studied in the complexation reaction of Zn2+ with [FeIII(CN)6]3-. The materials were characterized by Transmission Electron Microscopy (TEM) and Cyclic Voltammetry. The cyclic voltammograms of ZnH-1 and ZnH-2 showed a well-defined redox couple with formal potential (Eθ') = 0.94 ± 0.01 V (υ=20 mVs-1; KCl 1.0 M)) attributed to the redox process [FeII(CN)6]/[FeIII(CN)6] in the presence of Zn2+. The graphite paste electrode modified with ZnH-1 and ZnH-2 presents a sensitive and catalytic oxidation response for the determination of N-acetylcysteine respectively.
Keywords: Graphite paste electrode; N-acetylcysteine; Voltammetry; Zinc hexacyanoferrate (III) nanoparticles